DOSAGEM DE METABÓLITOS DE GLUCOCORTICOIDES E PROGESTERONA EM FEZES DE PAPAGAIO-VERDADEIRO (AMAZONA AESTIVA) - Caroline Junko Fujihara (Ciência Animal Brasileira, 2014)
The objectives of the present study were to evaluate fecal concentrations of metabolites of glucocorticoids, measured by enzyme immunoassay with a cortisol antibody and by radioimmunoassay with a corticosterone antibody, and progesterone by radioimmunoassay with a progesterone antibody in blue-fronted parrot (Amazona aestiva) after ACTH challenge. The adrenal stimulation with ACTH (25 UI/animal) resulted in an increase of fecal glucocorticoids metabolites concentration, but it did not affect the concentrations of fecal progesterone metabolites. Although there were no synchronized peaks of glucocorticoid metabolites excretion measured by enzyme immunoassay and radioimmunoassay, there were two peaks of excretion, one at 2-4 hours and other at 8-10 hours. Despite the occurrence of peaks, the analysis of fecal glucocorticoids metabolites and progesterone metabolites showed no effect of group (control and treatment), moment (hours of sampling) and sex.